2019
DOI: 10.1111/jog.14040
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in follicular fluid on embryos of patients undergoing assisted reproductive technology treatment

Abstract: Aim: Oxidative stress (OS) is defined as an imbalance between oxidants and antioxidants in favor of the oxidants, and the disruption of redox signaling leads to molecular damages. This study was conducted to clarify the effect of OS in individual follicular fluid (FF) on oocyte fertilization and embryonic division. Methods: A total of 124 patients who underwent assisted reproductive technology treatment in our hospital underwent intracytoplasmic sperm injection and 211 FF were collected. The ova were fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Numerous studies have previously found clear evidences of ROS and RNS overproduction in FF of IF with different clinical pathologies [33][34][35][36], although none of them performed the concomitant evaluation of the full profile of water-and fat-soluble antioxidants. In our group of IF, we found a significant decrease in FF concentrations of ascorbic acid, GSH, α-tocopherol, vitamin A, CoQ 10 , total carotenoids (p < 0.001), and a significant increase of MDA, 8-OH-dG, nitrite, and nitrate (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have previously found clear evidences of ROS and RNS overproduction in FF of IF with different clinical pathologies [33][34][35][36], although none of them performed the concomitant evaluation of the full profile of water-and fat-soluble antioxidants. In our group of IF, we found a significant decrease in FF concentrations of ascorbic acid, GSH, α-tocopherol, vitamin A, CoQ 10 , total carotenoids (p < 0.001), and a significant increase of MDA, 8-OH-dG, nitrite, and nitrate (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The main sources of ROS in the ovary are phagocytic macrophages, parenchymal steroidogenic cells, and endothelial cells [ 65 ]. Based on the role of ROS in folliculogenesis, the maturation of follicles, and ovulation, steroidogenic cells have potent antioxidant enzyme activity [ 66 ].…”
Section: Infertility and Oxidative Stressmentioning
confidence: 99%
“…GCs are involved in supporting and nourishing oocytes during follicular development and maturation (2,3). Oxidative stress (OS) caused by the increase of reactive oxygen species (ROS) levels has an important effect on oocyte and embryo quality (4,5). Previous study have found that the levels of ROS in the follicular fluid of patients with polycystic ovary syndrome (PCOS) and endometriosis (EMT) are significantly increased (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress (OS) caused by the increase of reactive oxygen species (ROS) levels has an important effect on oocyte and embryo quality (4,5). Previous study have found that the levels of ROS in the follicular fluid of patients with polycystic ovary syndrome (PCOS) and endometriosis (EMT) are significantly increased (4,6). In addition, within the healthy population, the total oxidative state and total antioxidant state in the follicular fluid also tend to be abnormal as the individual ages (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%